As interfaces da convivência da família em uma unidade de pronto socorro - Zani, Adriana Valongo; Real, Juliana de Moraes Vila; Golias, Andrey Rogério Campos; Mattos, Edlívia Dias de; Parada, Cristina Maria Garcia de Lima [UNESP]; Marcon, Sonia Silva (Universidade Estadual de Maringa, 2011)
The aim was to describe the positive and negative aspects in a family communication at an emergency care unit. This is a descriptive research with a qualitative approach. The sample consisted of 20 family members / caregivers of patients admitted to the emergency room of a university hospital. Data collection was carried out through semi-structured interviews applied during the period of May-June 2011. Data analysis was performed using the methodological framework of the Collective Subject Discourse which resulted in four themes: Lack of information compromising the family/health professional ties; The ideal model of information provided by the professional regarding the condition of the hospitalized relative; Assessment of information provided about hospital routines; and The role of the relative/companion. Therefore, for the patient and his family, communication is presented as a tool on the care given with the function of transmitting safety, respect and guidance. However when it is incomplete, it becomes a potential form of stress and dissatisfaction.

El objetivo del estudio fue describir los aspectos positivos y negativos de la comunicación de la familia con el equipo de salud en una unidad de urgencias. Se trata de una investigación descriptiva con abordaje cualitativo, realizada con veinte familiares/acompañantes de pacientes ingresados en urgencias de un hospital escuela. La recolección de datos se realizó a través de entrevistas semiestructuradas aplicadas a la familia durante el período mayo y junio de 2011 y analizados con base en el referencial metodológico del Discurso del Sujeto Colectivo. Con ello, resultaron cuatro ítems de discusión: “Ausencia de información comprometiendo el vínculo familiar/profesional y salud”; “El modelo ideal de informaciones provistas por el profesional sobre la condición del familiar hospitalizado; “Evaluación de las informaciones provistas sobre rutinas del hospital” y “El papel del familiar/acompañante”. Para el paciente y su familiar, la comunicación es una herramienta para el cuidado cuya función es transmitir seguridad, respeto y orientación, pero, cuando incompleta, se constituye en posibles causas de estrés e insatisfacción.

O objetivo do estudo foi descrever os aspectos positivos e negativos da comunicação da família com a equipe de saúde em uma unidade de pronto-socorro. Trata-se de uma pesquisa descritiva com abordagem qualitativa, realizada com vinte familiares/acompanhantes de pacientes internados no pronto-socorro de um hospital escola. Os dados foram coletados nos meses de maio e junho de 2011 por meio de entrevista semiestruturada e analisados com base no referencial metodológico do Discurso do Sujeito Coletivo, o que resultou em quatro itens de discussão: “Ausência de informações comprometendo o vínculo familiar/profissional de saúde”; “O modelo ideal de informações fornecidas pelo profissional sobre a condição do familiar hospitalizado”; “Avaliação das informações fornecidas sobre rotinas do hospital”; e “O papel do familiar/acompanhante. Para o paciente e seu familiar, a comunicação é uma ferramenta para o cuidado cuja função é transmitir segurança, respeito e orientação, porém, quando incompleta, constitui-se em potencial causa de estresse e insatisfação.
The interfaces of family coexistence in an emergency care unit
Las interfaces de la convivencia de la familia en una unidad de emergencias
Keywords: Communication; Family; Emergency medical services; Health personnel; Comunicación; Familia; Servicios médicos de urgencia; Personal de salud; Comunicação; Família; Serviços Mde Emergências; Pessoal de Saúde